Poster presentation Freshwater macroinvertebrate barcoding in Cyprus – First steps and new records - Vasquez Christodoulou, Marlen (My University, 2026)
Papatheodoulou A, Mora A, Pernecker B, Drakou K, Vasquez MI, Csabai Z, poster presentation, Freshwater macroinvertebrate barcoding in Cyprus – First steps and new records, poster presentation, Symposium for European Freshwater Sciences, Zagreb, Croatia, 30 June-5 July 2019.